Sistem Informasi Pendaftaran Siswa Baru Berbasis Web pada SMA Al-Hidayah - Elvira, Rika; Marbun, Nasib (LPPM STIKOM Tunas Bangsa, 2024)
SMA Al-Hidayah is one of the private high schools located in Medan. At Al-Hidayah High School, the new student registration procedure is still done manually, where all prospective new students must come directly to the school to fill out the registration form and submit the new student registration files needed by the school. The new student registration method applied at Al-Hidayah High School is considered inefficient to get many enthusiasts from outside Medan City. So that it can reduce the opportunity for SMA Al-Hidayah to get more new students in each new school year. The purpose of this research is to build a web-based new student registration information system equipped with a user-friendly interface, complete features, and good data integration at SMA Al-Hidayah. The system development method used in this research is the waterfall method. The result of this research is a web-based new student registration information system that can facilitate the process of registering new students at Al-Hidayah High School online.